The pn interaction and isospin symmetry - Cakirli, R. B.; Blaum, K.; Casten, R. F. (Frontiers in Physics, 2025)
A possible correlation between isospin symmetry/breaking and the average proton-neutron interaction of the last particles, δVpn, is discussed. This correlation is tested for Tz = ±1/2 mirror nuclei in terms of a differential of δVpn, Δ(δVpn), and their low-lying excited levels. Some nuclei, whose mass measurements will be useful for future studies, are suggested.